Inteligencias múltiples y su incidencia en el proceso de enseñanza–aprendizaje de los estudiantes de educación básica elemental de la escuela “Estenio Burgos Galarza”, San Carlos, cantón Quevedo, período lectivo 2021- 2022 - Navarrete Arechua, Silvia Maribel (2022)
The objective of this study is to analyze the different multiple intelligences that are developed in the teaching-learning process of the Elementary Basic General Education students of the Estenio Burgos Galarza School, in order to address the cognitive diversity that occurs in the classroom. This work addresses the problem of the limitations of multiple intelligences in teaching practice, for which it proposes a training plan on multiple intelligences, with this proposal it is intended to strengthen the most used intelligences in order to enhance the less developed in training academic and identify strategies that promote the transformation of education in a creative and innovative space. The present work was carried out with the purpose of contributing to the improvement in the teaching-learning process, it is based on the Theory of Multiple Intelligences, this constructivist paradigm benefits education. The research methodology is framed in the qualitative-quantitative approach, bibliographic and field modality, descriptive level, for the data collection the analytical-synthetic, deductive-inductive methods were used. To support this work, data collection was carried out through direct observation, interview and survey, the study population is made up of 1 manager, 16 teachers and 69 students